Staphylococcus aureus Colonization Among Household Contacts of Patients With Skin Infections: Risk Factors, Strain Discordance, and Complex Ecology - Miller, Loren G.; Eells, Samantha J.; Taylor, Alexis R.; David, Michael Z.; Ortiz, Nancy; Zychowski, Diana; Kumar, Neha; Cruz, Denise; Boyle-Vavra, Susan; Daum, Robert S. (Clinical infectious diseases, 2012)
Background. The USA300 methicillin resistant Staphylococcus aureus (MRSA) genetic background has rapidly emerged as the predominant cause of community-associated S. aureus infections in the U.S. However, epidemiologic characteristics of S. aureus household transmission are poorly understood. Methods. We performed a cross-sectional study of adults and children with S. aureus skin infections and their household contacts in Los Angeles and Chicago. Subjects were surveyed for S. aureus colonization of the nares, oropharynx, and inguinal region and risk factors for S. aureus disease. All isolates underwent genetic typing. Results. We enrolled 1162 persons (350 index patients and 812 household members). The most common infection isolate characteristic was ST8/SCCmec IV, PVL+ MRSA (USA300) (53%). S. aureus colonized 40% (137/350) of index patients and 50% (405/812) of household contacts. A nares-only survey would have missed 48% of S. aureus and 51% of MRSA colonized persons. Sixty-five percent of households had >1 S. aureus genetic background identified and 26% of MRSA isolates in household contacts were discordant with the index patients' infecting MRSA strain type. Factors independently associated (P < .05) with the index strain type colonizing household contacts were recent skin infection, recent cephalexin use, and USA300 genetic background. Conclusions. In our study population, USA300 MRSA appeared more transmissible among household members compared with other S. aureus genetic backgrounds. Strain distribution was complex; >1 S. aureus genetic background was present in many households. S. aureus decolonization strategies may need to address extra-nasal colonization and the consequences of eradicating S. aureus genetic backgrounds infrequently associated with infection.